O sofista de Platão: ontologia, discurso e alteridade - Oliveira, Tiago Fernando Soares de (2019)
This dissertation intends to investigate how Plato understands the relation between the discursive and ontological scopes in the Sophist. The working hypothesis is that such a relationship is enabled by the theory of participation of the gene. The dramatic section of this work presents an unusual alliance between the thought of Parmenides of Eleia with the sophistry, generated by the definition of the sophist as a producer of false discourse. However, for there to be falsehood it is necessary to affirm that in some way non-being is, which was absolutely forbidden by the Parmenidean doctrine. Faced with this, Plato is required to conduct a critical examination of his Eleatic heritage to propose an ontology capable of embracing the notion of otherness. Without a principle of difference, it is impossible for the discourse to say of things what they are. The participation of the supreme genres will be the ontological paradigm that will instantiate both the mixture of entities and the relation between the names that constitute a statement, that is, predication. Discourse, in this perspective, has a structural similarity with the real and, therefore, can be taken as a complex symbol that intends to represent reality from its parts and not in block. Thus, it will be possible to distinguish the meaning of the statement from its truth-value, since false discourse, although significant because it is syntactically well constructed, will establish a relation between linguistic symbols that does not correspond to any real interweaving. By dissipating the paradox of false discourse, Plato determines the conditions of possibility of any and all speech, and against sophistic relativistic pretension establishes philosophy as a dialectical practice capable of attaining objective knowledge of being.